Assessing the Antecedents and Consequence of Enterprise Transformation: A Quantitative Approach - Song, Haiyan; Hongsuchon, Tanaporn; Kittikowit, Santhaya; Dong, Zhe (Frontiers in Psychology, 2022)
With the continuous recession of economic globalization and the increasing market competition, enterprise transformation gradually becomes the theme of enterprise management. Although more and more scholars and companies have paid attention to the importance of enterprise transformation, most of the research on enterprise transformation is still at the qualitative level of theoretical descriptions, and lacks a comprehensive consideration and empirical research on the motivation and performance of enterprise transformation. The research on enterprise transfor-mation is still at the qualitative level of theoretical descriptions, but lacks a comprehensive con-sideration and empirical research on the motivation and performance of enterprise transformation. In view of this, this study analyzes the overall driving effect of technological innovation and its internal and external environment on enterprise transformation from the perspective of the driv-ers of enterprise transformation, and analyzes in depth the causes and consequences of enterprise transformation for different industries (construction and real estate industries). The study also an-alyzes the antecedents and consequences of enterprise transformation and its differences in dif-ferent industries (construction and real estate). In this study, a sample of middle and senior man-agement of 10 companies with a valid sample of 401 was sampled, and structural equation mod-eling was applied to Mplus 7.4. The results show that competitive advantage, technological in-novation, and market pressure significantly affect enterprise transformation, which is an anteced-ent of corporate performance. Further, the results of the multiple- group analysis also revealed some significant differences between the theoretical models of the construction and real estate communities. Finally, suggestions are made based on the findings.